Qualification of patients with initial infectious outbreak in oral cavity for surgical procedures. Prognosis of teeth after root canal treatment, in oral sanation - Winiarski, Marcin; Kodzik, Marta; Bojkowski, Maksymilian; Winiarska, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2016)
The oral cavity is in many cases the source of focal infections. During the sanation of the oral cavity we eliminate the initial outbreak of infectious. In most cases, diagnosis and treatment does not arouse dentist’s doubts. The dilemma in many cases become teeth after endodontic treatment. Particularly among patients with absolute indications for sanation, even properly cured endodontic teeth are often destined for extraction . One should consider the possibility of an objective evaluation of the teeth with filled root canals so that they can remain in the patient’s mouth without being infectious outbreak.